Gregg typing : series eight : keyboarding and processing documents - Lloyd, Alan C. (New York : Gregg Division/McGraw-Hill, 1987)
A textbook for a two-semester general course in typewriting for the secondary school. Includes formatting of correspondence, reports, tables, and other forms.
1. General course -- 2. Advanced course.
2
Keywords: Typewriting